On the Economics and Biology of Trust - Ernst Fehr (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
In recent years, many social scientists have claimed that trust plays an important role in economic and social transactions. Despite its proposed importance, the measurement and the definition of trust seem to be not fully settled, and the identification of the exact role of trust in economic interactions has proven to be elusive. It is still not clear whether trust is just an epiphenomenon of good institutions or whether it plays an independent causal role capable of shaping important aggregate economic outcomes. In this paper, I rely on a behavioral definition of trust that enables us to relate it to economic primitives such as preferences and beliefs. I review strong biological and behavioral evidence indicating that trusting is not just a special case of risk-taking, but based on important forms of social preferences such as betrayal aversion. Behaviorally defined trust also opens the door for understanding national and ethnic trust differences in terms of differences in preferences and beliefs, and it suggests ways to examine and interpret a causal role of trust.
Keywords: C7; D0; D2; D7; D8; 330; trust; preferences; beliefs; biological basis